UJI PEMBERIAN BEBERAPA KONSENTRASI GLISIN PADA MEDIA VACIN AND WENT (VW) TERHADAP PERTUMBUHAN PLANTLET ANGGREK (Dendrobium sp.) SECARA IN VITRO - Sucandra, Adi; Silvina, Fetmi; Yulia, Arnis En (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aim is to know the influence and get a glycine concentration on vacin and went (VW) medium that giving the best growth of Dendrobium orchid plantlet by in vitro. This research was conducted in Plant Biotechnological Laboratory of Farm Faculty, University of Riau, Pekanbaru from March till June 2014. This research is an experiment used a Completely Randomized Design (CRD) which arranged in six levels and three repetitions. The treatment is giving a several glycine concentration started with without glycine, 1 mg glycine/l, 2 mg glycine/l, 3 mg glycine/l, 4 mg glycine/l and 5 mg glycine/l. The data obtained were statistically analyzed using analysis of variance and Duncan's New Multiple Range Test (DNMRT) at the level of 5%. The result showed that giving a several glycine concentration was not significant for all parameters, but giving glycine with concentration 4 mg/l showed the best result to the height of plant, leaf amount, root amount and visual view of the Dendrobium orchid plantlet. Â Keyword: Dendrobium, Orchid Plantlet, Glycine